The Effect of Low-Dose Ketamine in Treating Acute Asthma Attack; a Randomized Clinical Trial - Esmailian, Mehrdad; Koushkian Esfahani, Mahboubeh; Heydari, Farhad (Archives of Academic Emergency Medicine, 2018)
Introduction: Efficient treatment of asthma can play an important role in controlling asthma attacks, rapid recovery and decrease of patient mortality. Therefore, in the present study the therapeutic effect of low-dose ketamine is evaluated in patients with acute asthma attack. Methods: In the present single-blind, randomized clinical trial with placebo control, the effect of low-dose intravenous ketamine in treating 18 to 85 year-old asthmatic patients who presented to the emergency department was evaluated. Peak expiratory flow rate (PEFR) and the patients’ response to treatment were measured before and 1 hour after treatment. Additionally, using SPSS 22.0, effectiveness of ketamine with 0.3, 0.4, and 0.5 mg/kg doses followed by infusion of the same dose during 30 minutes were compared with placebo. Results: 92 patients were enrolled (59.8% female, mean age 48.5 ± 13.9 years). 15 (16.3%) patients were treated with 0.3 mg/kg ketamine, 14 (15.2%) with 0.4 mg/kg, and 16 (17.4%) with 0.5 mg/kg doses. Mean PEFR was 336.2 ± 101.5 liters in the placebo group and 345.8 ± 84.7 liters in the ketamine group before intervention (p = 0.6), while after intervention, they were 352.1 ± 101.2 and 415.8 ± 76.2 liters, respectively (p = 0.001). Ketamine treatment with 0.4 and 0.5 mg/kg doses led to a higher increase in PEFR compared to 0.3mg/kg dose (df: 3, 88; F = 23.8; p < 0.001). Conclusion: It seems that administration of 0.4 - 0.5 mg/kg doses of intravenous ketamine followed by infusion of the same dose during 30 minutes can be effective for rapid recovery of PEFR in patients with mild to moderate asthma.